2019
DOI: 10.1016/j.ptsp.2018.10.011
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of injury in English Professional Football players: A cohort study

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
3
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 17 publications
5
57
3
11
Order By: Relevance
“…The video component of this article can be found at https://www.jove.com/video/60857/ 14,15,16,17 . Furthermore, the number of athletes that sustain a hamstring strain injury rises each year 18,19 , despite that multiple programs have been introduced to prevent hamstring strain injuries 12,13,20,21…”
Section: Video Linkmentioning
confidence: 99%
“…The video component of this article can be found at https://www.jove.com/video/60857/ 14,15,16,17 . Furthermore, the number of athletes that sustain a hamstring strain injury rises each year 18,19 , despite that multiple programs have been introduced to prevent hamstring strain injuries 12,13,20,21…”
Section: Video Linkmentioning
confidence: 99%
“…Of the 51 studies (one of the 51 articles contained two studies [70]), 44 reported recurrent injuries as either a number, percentage, incidence or a combination of these. Almost half of the articles, 21 of the 44, reported both the number and the percentage of recurrent injuries [2, 25, 38, 41-43, 45, 47, 48, 50, 54, 55, 58, 59, 61, 64, 67, 76, 78, 80, 81]; 13 only reported the percentage [27,37,44,46,49,51,52,62,68,69,71,74,77]; three only reported the number [40,66,79]; five reported the number, percentage and incidence [4,30,39,53,63]; and two only reported the incidence [57,60]. The number of recurrent injuries ranged from one [79] to 3016 [59], the proportion ranged from 5.5 [81] to 48% [59] and the incidence ranged from 0.5 to 2.55 recurrent injuries per 1000 h [37,53].…”
Section: Recurrent Injuriesmentioning
confidence: 99%
“…One of the main findings in this systematic review was that 30 of the articles were excluded from data extraction as they failed to report recurrent injuries at all, even when following the definitions and data collection procedures outlined by a consensus statement. Within the studies that did report injury recurrence, a number of studies only identified the proportion within the total number of injuries [27,37,44,46,49,51,52,60,62,68,69,74,77], providing insufficient detail about the nature or consequence of the recurrent injuries. Additionally, only ten studies provided detail of the body area associated with recurrent or subsequent injuries, meaning appropriate (re)injury prevention strategies cannot be recommended.…”
Section: Definition Of Recurrent Injuriesmentioning
confidence: 99%
“…Thirty-one to 41% of all injuries in soccer involve the muscles, with most occurring in the thigh [ 1 – 3 ]. The hamstring muscles (comprising the biceps femoris, semimembranosus, and semitendinosus muscles) account for up to 37% of all muscle injuries in soccer players, a number on the increase.…”
Section: Introductionmentioning
confidence: 99%